Pemaknaan Nilai Perjuangan dan Kasih Sayang Ibu Asuh dalam Film Air Mata Di Ujung Sajadah - Oktaviani, Cindy; ., Mayasari; Ramdhani, Muhamad (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Some Indonesians think that the care of a child by a foster mother will not be as good as when raised by a biological mother. Through this movie, Key Mangunsong as the director of this movie wants to convey the meaning of family, especially mothers, in caring for educating children. The purpose of this research is to find out how the representation of the meaning of the struggle for love of a foster mother in the movie air mata di ujung sajadah. This research uses a qualitative method using the Roland Barthes semiotic approach and focuses on the character Yumna as a subject who becomes a foster mother by looking at aspects of denotation, connotation, and myth. There are 9 scenes in this study which are the material for data analysis. In addition, data collection was carried out by means of observation, document study, and literature study. The results of this study show that foster mothers can educate their foster children by giving abundant love to their children.